Defect analysis of sputter grown cupric oxide for optical and electronics application. (18th November 2015) - Dalapati, Goutam Kumar; Kajen, Rasanayagam Sivasayan; Masudy-Panah, Saeid; Sonar, Prashant
Abstract: We have studied the defect density and defect level of sputter grown cupric oxide (CuO) for optical and electronic applications. A deep level transient spectroscopy (DLTS) technique has been employed to study the defect density in the CuO thin film deposited by sputtering. The DLTS studied showed that the defect density significantly reduced for the film grown at a high working pressure. It has also been shown that doping density increases for the film grown at a high working pressure. Transmission electron microscopy analysis revealed the improvement of the crystal quality of the CuO thin film prepared at the high working pressure. The band gap of sputter grown CuO was found to be 1.4 eV with an absorption coefficient of 10 4 cm −1 . From a photoelectron spectroscopy measurement, it was found that the work function for CuO was 5.2 eV. The present work reveals the importance of CuO for optical and electronic device applications.